1987
DOI: 10.1111/j.1365-2923.1987.tb00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a dangerous answer subtest within a subspecialty certifying examination

Abstract: Previous studies have been reported suggesting that a population of candidates for specialty board certification can be identified who pass the certification examination but who give an unduly high number of 'dangerous' responses, indicating their acceptance of actively harmful actions. To confirm these results, a retrospective analysis was undertaken of a Subspecialty Board of Nephrology certification examination. Experts identified a subtest of 75 dangerous answers. The performance of candidates on this subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Replicating aspects of previous findings in different student groups increases the generalisability of the results. Previously, others reported that the number of unsafe responses is proportional to the numbers of incorrect responses, and therefore this additional metric adds nothing [ 25 , 27 ]. However, all previous investigations have been retrospective, where the candidates were not given any scoring disincentive for responding unsafely [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Replicating aspects of previous findings in different student groups increases the generalisability of the results. Previously, others reported that the number of unsafe responses is proportional to the numbers of incorrect responses, and therefore this additional metric adds nothing [ 25 , 27 ]. However, all previous investigations have been retrospective, where the candidates were not given any scoring disincentive for responding unsafely [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concern has also been raised about those who have sufficiently good examination performance to score above a pass threshold in assessments but whose incorrect responses are considered dangerous, possibly demonstrating a lack of consideration of consequences of decisions [ 25 28 ]. Thus, getting enough correct responses to pass is not offset by noting their incorrect dangerous responses.…”
Section: Introductionmentioning
confidence: 99%
“…They then compared scores on the subset to composite scores, to find out whether any candidates who passed had `failed' the subset. In the American Board of Internal Medicine's Subspecialty Board of Nephrology, the 6·6% of certified candidates who `failed' the subset had no demographic differences to those who passed 69 . Further analysis of subset to composite score corrected for low reliabilities revealed that the subset did not measure unique properties.…”
Section: Examination Factorsmentioning
confidence: 96%
“…Two of the included papers, both from the USA Specialty Boards, one nephrology, 69 the other anaesthetics, 63 investigated the impact of separately scoring subsets of written questions. The authors identified a subset of questions with answers that could, if selected incorrectly, be potentially dangerous to patients.…”
Section: Examination Factorsmentioning
confidence: 99%
“…For example, Webster, Goldfarb, Norcini, Shea, and Murray (1987) studied the relationship between the number of dangerous options selected on the American Board of Internal Medicine's Subspecialty Board of Nephrology multiple-choice examination and overall performance on the test. They found that most examinees selecting dangerous treatment options performed poorly on the rest of the test.…”
mentioning
confidence: 99%